FUN READING ADVENTURE: INCREASE READING INTEREST THROUGH PICTURED STORIES IN ELEMENTARY SCHOOL CHILDREN - Susiani, Rini; Suryani, Suryani; Inayah, Nurul; Humairah, Mila; Zhavira, Alifya (Universitas Muhammadiyah Aceh, 2025)
Reading is a fundamental skill that plays a crucial role in the academic development of elementary school students. However, reading interest in rural areas remains relatively low. This community service program aims to improve the reading interest of children in Seubam Cot Village through the Fun Reading Adventure approach using picture stories. The implementation method consisted of four stages: needs identification, the development of picture story modules, interactive reading activities, and evaluation through observation and interviews. The results show several significant outcomes. First, students’ literacy skills improved through the integration of texts and illustrations that facilitated comprehension. Second, picture stories enhanced students’ intrinsic motivation to read by presenting narratives in an engaging and enjoyable format. Third, the reading experience enriched children’s emotional and social aspects by fostering empathy and self-confidence in communication. Fourth, the program supported the development of social skills through group discussions and interactions with peers and parents. This program demonstrates that the use of picture stories can effectively promote reading habits in young learners at the elementary level.